Frequent exposure to suboptimal temperatures in vaccine cold-chain system in India: results of temperature monitoring in 10 states - Manoj V Murhekar; Srihari Dutta; Ambujam Nair Kapoor; Sailaja Bitragunta; Raja Dodum; Pramit Ghosh; Karumanagounder Kolanda Swamy; Kalyanranjan Mukhopadhyay; Somorjit Ningombam; Kamlesh Parmar; Devegowda Ravishankar; Balraj Singh; et al.
Objective To estimate the proportion of time the vaccines in the cold-chain system in India are exposed to temperatures of < 0 or > 8 °C. Methods In each of 10 states, the largest district and the one most distant from the state capital were selected for study. Four boxes, each containing an electronic temperature recorder and two vials of diphtheria, pertussis and tetanus vaccine, were placed in the state or regional vaccine store for each study state. Two of these boxes were then shipped - one per facility - towards the two most peripheral health facilities where vaccine was stored in each study district. The boxes were shipped, handled and stored as if they were routine vaccine supplies. Findings In state, regional and district vaccine stores and peripheral health facilities, respectively, the temperatures in the boxes exceeded 8 °C for 14.3%, 13.2%, 8.3% and 14.7% of their combined storage times and fell below 0 °C for 1.5%, 0.2%, 0.6% and 10.5% of these times. The boxes also spent about 18% and 7% of their combined times in transit at < 0 and > 8 °C, respectively. In shake tests conducted at the end of the study, two thirds of the vaccine vials in the boxes showed evidence of freezing. Conclusion While exposure to temperatures above 8 °C occurred at every level of vaccine storage, exposure to subzero temperatures was only frequent during vaccine storage at peripheral facilities and vaccine transportation. Systematic efforts are needed to improve temperature monitoring in the cold-chain system in India.